The Effect of Salted Fish Consumption on Blood Pressure in Postpartum Mothers on Days 1-28 - Sri Sudharmi; Nila Widya Keswara (Lembaga Pengembangan Kinerja Dosen, 2025)
The postpartum period is an important time for the mother's physiological recovery after childbirth, during which various bodily changes are still ongoing and health risks, including changes in blood pressure, may occur. One factor that is thought to affect blood pressure during the postpartum period is dietary patterns, particularly high sodium intake. Salted fish is a food commonly consumed by the community and is known to have a high salt content. This study aims to analyze the effect of salted fish consumption on blood pressure in postpartum mothers from day 1 to day 28. This study used a quantitative approach with an analytical observational design through a cross-sectional method. The study sample consisted of 20 postpartum mothers on days 1–28 who were selected using purposive sampling. The independent variable was salted fish consumption, while the dependent variable was the systolic blood pressure of postpartum mothers. Data were collected through interviews using a structured questionnaire and blood pressure measurements with a standard tensiometer. Data analysis was performed using univariate and bivariate methods. The Shapiro–Wilk normality test showed that the data were not normally distributed, so the analysis was continued with the Wilcoxon test. The results of the study show a significant difference between systolic blood pressure before and after exposure to salted fish consumption, indicating that consumption of foods high in salt affects changes in blood pressure in postpartum women. This study concludes that salted fish consumption has the potential to affect the blood pressure of postpartum women. Therefore, nutrition education related to limiting the intake of foods high in salt during the postpartum period needs to be improved as part of efforts to prevent postpartum hypertension.